Flow behavior and syneresis of ball milled rice starch and their correlations with starch structure - González, Luciana Carla (2021)
The effects of milling energy (0.26–4.08 kJ/g) on starch structure, flow behavior and syneresis of starch dispersions (4–8% w/v) were investigated. Crystallinity loss of starch (XRD analysis) during milling could be mathematically related with the increase of 1047 cm−1/1022 cm−1 FT-IR intensity ratio (Ri) and it was also reflected by the changes in the shape and surface roughness of starch granules (SEM micrographs). Starch dispersions showed a Newtonian or pseudoplastic flow pattern dependent on starch concentration and milling energy. Consistency of starch dispersions (4 and 6%) remained constant during refrigerated storage only for severely milled starch. Syneresis diminished with increasing milling energy and starch concentration; it could be minimized (4% and 4.08 kJ/g) or completely eliminated (8% and 1.04 kJ/g). Significant correlations of Ri with consistency index and syneresis were found. Ball milling notably improved the suitability of starch as an ingredient in fluid or viscous foodstuffs.